2022
DOI: 10.1080/0886022x.2022.2130802
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between platelet distribution width and new-onset cardiovascular disease events in patients with peritoneal dialysis

Abstract: Objectives The global mortality rate from chronic kidney disease (CKD) has increased over the past two decades. Typically, peritoneal dialysis (PD) remains a useful alternative treatment for end-stage renal disease. Cardiovascular disease (CVD) is the main complication in PD patients. In terms of prognosis, it is reported that platelet distribution width (PDW) can predict adverse CVD events. However, the relationship between PDW and new-onset CVD in PD patients is not clear. This study aimed to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…As the most common complication, CVD is currently considered to be the main cause of death in patients with chronic kidney disease (CKD) and PD [ 3 , 4 ]. Recent studies have suggested that inflammation and thrombosis play a critical role in the occurrence of CVD in CKD patients [ 7 , 12 ]. Platelets are not only a key component in regulating hemostasis and thrombosis, but also related to inflammation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the most common complication, CVD is currently considered to be the main cause of death in patients with chronic kidney disease (CKD) and PD [ 3 , 4 ]. Recent studies have suggested that inflammation and thrombosis play a critical role in the occurrence of CVD in CKD patients [ 7 , 12 ]. Platelets are not only a key component in regulating hemostasis and thrombosis, but also related to inflammation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that inflammation and thrombosis play a critical role in the occurrence of CVD in CKD patients [ 7 , 12 ]. Platelets are not only a key component in regulating hemostasis and thrombosis, but also related to inflammation [ 12 ]. PDW is a specific marker reflecting platelet activity [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation